Clinical impact of intraoperative frozen sections during nerve-sparing radical prostatectomy - Heinrich, Elmar; Schön, Georg; Schiefelbein, Frank; Michel, Maurice Stephan; Trojan, Lutz (World journal of urology, 2010)
Enhanced surgical techniques and standardised selection criteria have led to a higher rate of nerve-sparing (NS) radical prostatectomy (RP) procedures. The aim of this study was to evaluate the clinical value of intraoperative frozen sections (IFS) during nerve-sparing radical prostatectomy (NSRP).